Le point de vue critique des ecrits psycho-sociologiques (1889-1905) de Augustin Hamon
Photocopy. Reprint: Studies in the history of psychology and the social sciences : proceedings of the First European Meeting of Cheiron International Society for the History of the Behavioral and Social Sciences held at Amsterdam (F.U.), september 15-17, 1982 (Leiden: Rijksuniversiteit, 1983) p. 31-52.